On the Efficacy of Separating Control and Data into Different Frequency Bands - Kyasanur, Pradeep; Padhye, Jitu; Bahl, Victor (Second International Conference On Broadband Networks (BROADNETS) 2005, 2005)
Radio spectrum allocated for use in unlicensed wireless networks is distributed across non-contiguous frequency bands. Existing MAC protocols, like IEEE 802.11, operate only in contiguous bands. Several small slices of frequency are available in lower frequency bands that are not utilized. We propose utilizing a sliver of unused spectrum in the lower frequency band as a low rate control channel to improve the capacity of infrastructure and multi-hop wireless networks. The proposed Control Channel based MAC Protocol (C2M)increases the throughput by moving the contention resolution overheads to the separate low rate channel. We allow simultaneous channel contention and data transmission by incorporating advance reservation on the control channel, and data aggregation on the data channel. Simulation results show that compared to IEEE 802.11, C2M significantly improves network performance.